Zinc seed priming improves salt resistance in maize. (8th March 2018) - Imran, M.; Boelt, B.; Mühling, K.‐H.
Abstract: Salt stress is a major yield‐limiting factor in crops by reducing nutrient uptake and plant growth. Under salt stress, decreased water and nutrient uptake results in nutrient imbalance in plants. In addition, at high pH in saline conditions, solubility of minerals is also reduced leading to low availability of certain nutrients. Perspectives to overcome these limitations by Zn seed priming were studied with maize plants exposed to NaCl as salt stress. Maize seeds were primed for 24 hr in deionized water and 4 mm ZnSO4 ·7H2 O solution (ZnP) and subsequently air‐dried at room temperature before further use. The DTZ (diphenylthiocarbazone) staining method was used for showing Zn 2+ localization in the seeds. Zn 2+ and other nutrient concentrations in unprimed, water and ZnP seeds and maize plants were analysed by inductively coupled plasma mass spectroscopy (ICP‐MS). Maize plants (cv. Sun star L.) were grown for 3 weeks in complete nutrient solution with or without salt stress (100 mm NaCl) under glasshouse conditions. Seed Zn 2+ contents were increased after ZnP treatment by 600%. In maize seeds, most of the primed Zn 2+ accumulated in the outer tissues (particularly, aleurone layer) of maize seed. Zn priming decreased the injurious effects of salt stress on plant growth. Under salt stress conditions, biomass production of plants from ZnP treatments was 25% higher compared to water priming treatment. Zn seed priming also improved mineral nutrient status of plants grown in both control and salt stress conditions. Plants from ZnP treatments also showed higher accumulation of Na + in the shoots. This offers perspectives for using Zn seed priming for improving early seedling development and plant nutrient status of maize under salt stress conditions.